Gas Separation Performance through Carbon Membrane: The Effect of Polymer Composition - Mohd Syafiq, Sharip; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; Mohd Nizar, Mhd Razali (Akademia Baru Publishing (M) Sdn Bhd, 2020)
A comprehensive requirement in terms of efficient strategies in collecting reasonably high purity of H2 is predicted due to the development of hydrogen (H2)-based economy. The purpose of a H2- selective membrane is to exploit the high diffusivity features of H2 and also to limit the consequence of lower solubility. Owing by its highly permeable and selective characteristics, carbon membranes provide great potential in gas separation industry. Hence, the objective of this study is to examine the effect of carbonization parameter, in particular the composition of polymer on the properties of gas separation. Matrimid 5218 was used as a precursor for the fabrication of carbon tubular membrane to manufacture a carbon membrane with high quality through the process of carbonization. The surface of tubular ceramic tubes was coated with polymer solution via dip-coating technique. The dip-coating method provides an excellent potential in the manufacture of defect-free carbon membrane. The resultant Matrimid 5218-based carbon tubular membranes were characterized in terms of structural morphology using scanning electron microscopy (SEM), chemical structure using Fourier transform infrared (FTIR), thermal stability, and gas permeation properties using pure gas permeation system. The best formulation for Matrimid 5218-based carbon tubular membrane fabrication was shown by the polymer solution containing 15wt% of Matrimid 5218. The highest H2/N2 selectivity of 401.08±2.56 was achieved by carbon membrane carbonized at 800°C with 2°C/min of heating rate.